Density and abundance of Rhea pennata garleppi (Struthioniformes: Rheidae) in the Puna ecoregion of Argentina - Marinero, Nancy Veronica (2014)
Background: Rhea pennata is classified internationally as a near-threatened species, with the subspecies R. p. garleppi being listed as endangered. Finding: The aim of this study was to provide updated information on the density and abundance of R. p. garleppi in the southern Puna ecoregion of Argentina. Density was estimated indirectly on the basis of monthly feces counts during 2011 and 2012, using line-transect surveys. Monthly abundance was calculated by multiplying the density of each month by the area of the reserve (400 km2 ). Population size range was calculated considering the average of the months with the highest abundance (and density) as the upper limit and the average of the months with the lowest abundance (and density) as the lower limit. The population size of this subspecies varied between 300 individuals (±60), with a density of 0.75 individuals/km2 (±0.15) during the non-breeding season, and 188 individuals (±40), with a density of 0.47 individuals/km2 (±0.10), during the reproductive season. Conclusion: This work shows the highest density record for R. p. garleppi so far and highlights changes in population size related to life history characteristics of rheas, as well as human factors that negatively affect the survival of wild populations